Ganglion Cell Complex Evaluation in Exudative Age-Related Macular Degeneration after Repeated Intravitreal Injections of Ranibizumab. (8th June 2015) - Perdicchi, Andrea; Peluso, Giacomo; Iacovello, Daniela; Balestrieri, Marco; Delle Fave, Martina; Abdolrahimzadeh, Solmaz; Scuderi, Gian Luca; Fenicia, Vito; Recupero, Santi Maria
Abstract : Purpose . To detect the effects of intravitreal ranibizumab injections on GCC in patients with wet AMD. Methods . 32 wet AMD eyes were selected and submitted at three ranibizumab injections. RTVue-OCT GCC and MM5 protocol were performed before treatment and twenty days after each injection. Results . At baseline mean GCC thickness was 93.9 ± 18.5 μ m. Twenty days after each intravitreal injection it was, respectively, 85.8 ± 10.1, 86.5 ± 9.3, and 91.1 ± 11.5 μ m, without statistical significance. A significant improvement in visual acuity ( P = 0.031) and a reduction of mean foveal ( P = 0.001) and macular thickness ( P = 0.001) were observed. Conclusion . The clinical results confirm therapeutic efficacy of intravitreal injections of ranibizumab in wet AMD. A contemporary not statistically significant reduction of GCC thickness suggests that the loading phase of ranibizumab does not have any toxic effects on ganglion cell complex.